Electronic tendering in public procurement : a case study on Local Government Engineering Department (LGED) - Rahim, Md. Abdur (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.